A passagem do primeiro ao segundo dualismo pulsional e o problema da constituição do Eu: um estudo sobre Freud - Salgado, Gustavo Campassi (Universidade Federal de São Carlos, 2024)
From the very beginning of the development of the Trieb as a psychoanalytic concept, there was a need within the theory to sustain a dualism in terms of the classification of drives. This dualism initially took place between the so-called sexual drives and the self-preservative drives. In its initial conception, the drive is understood as a stimulus (Reiz) which, coming from the body, its source (Quelle), will generate a urge (Drang), aimed at satisfaction (Befriedigung) through the annulment of the state of stimulation. The drive will then enter the psychic field through a representative (Repräsentant), in the form of affection (Affekt) and representation (Vorstellung). Conceiving this movement of drive circulation becomes more complex after 1920 if we take into account that, at this point in the construction of the psychoanalytic discourse, we have the introduction of a drive for which there is no representation in the psyche, in other words, without the element that configures the drive's entry into the psychic field: the death drive (Todestrieb). If we assume, with the Freudian text, that it is through the need for drive circulation that the psychic apparatus is formed, and that representation is a privileged moment in this circulation, the introduction of a drive whose characteristic is the absence of this element opens up a fruitful field of investigation. Bearing in mind that in the second drive dualism the ultimate goal of the drive is its total annulment as a state of stimulation and that the psychic instance called the "I" arises late and in close relation to the need for drive circulation and the establishment of a representational field in the psyche, this dissertation is an investigation into the constitution of the "I" in the light of the second moment of Freudian drive doctrine, starting initially with a preliminary investigation of the transition from the first to the second dualism.
The transition from the first to the second drive dualism and the problem of the constitution of the I: a study on Freud
Keywords: Freud; Metapsicologia; Pulsão; Psicanálise; CIENCIAS HUMANAS::FILOSOFIA::HISTORIA DA FILOSOFIA; CIENCIAS HUMANAS::PSICOLOGIA::FUNDAMENTOS E MEDIDAS DA PSICOLOGIA